Are the individual and collective roles of financial reporting quality measures the same? Evidence in the context of information uncertainty. Issue 2 (3rd April 2019) - Hesarzadeh, Reza
ABSTRACT: An implicit premise of much empirical research is that the individual role and the collective role of a financial reporting quality (quality) measure are the same, in the sense that the impacts of a quality measure on a dependent variable, without and with considering the trade-off/interaction and combination with other quality measures, are the same. I question whether the two roles are really the same. I conduct my investigation in the context of information uncertainty. I employ conventional statistical methods to explore the individual role of quality measures and use the decision tree method to explore their collective role. My findings reveal some significant differences between the two roles. Further, the findings indicate that the collective role of a quality measure can differ in accordance with the group to which the quality measure belongs. Overall, the findings reject this premise that the individual and collective roles of quality measures are the same. Moreover, the findings enhance the understanding of the collective role of quality measures.